Students’ Perception of Online Learning During the Covid-19 Pandemic at SMP Swasta Sinar Sentosa - Farida Hanum Pakpahan; Erika Sinambela; Sondang Manik; Kammer Tuahman Sipayung (Jurnal Scientia, 2022)
The purpose of this study is to find out how students at SMP Swasta Sinar Sentosa felt about online learning during the covid-19 pandemic. This study uses a quantitative approach to conduct a descriptive investigation. A survey method was used in this study. The information was gathered utilizing a questionnaire at SMP Swasta Sinar Sentosa, 26 of the ninth graders took part in this investigation. The researcher discovered that learning online during the covid-19 pandemic is less effective than learning in the classroom. The students showed positive and negative perceptions. Online learning at SMP Swasta Sinar Sentosa, students learn through a variety of applications, including WhatsApp, Zoom, and Google Classroom. Based on the analysis of the data, the conclusion can be drawn that students’ perceptions of online learning during the covid-19 pandemic have positive perceptions and negative perceptions. This can be seen from the percentage of the data based on some dimensions. Perception related to the dimension of teaching material with a percentage of 71,79 % agree perception related to the dimension of atmosphere or learning environment with a percentage of 74,03 %disagrees, and perception related to students’ interaction with a percentage of 69,22 % disagree. From the finding that has been discussed, the students cannot adapt and adjust to all the dimensions contained in the online learning process.